2019
DOI: 10.1371/journal.pone.0226041
|View full text |Cite
|
Sign up to set email alerts
|

Women’s decision-making power and undernutrition in their children under age five in the Democratic Republic of the Congo: A cross-sectional study

Abstract: Undernutrition in children remains a major global health issue and the prevalence of undernutrition in children under age five in the Democratic Republic of the Congo (DRC) is among the highest in the world. Both biological and socioeconomic factors contribute to undernutrition, and the literature reports an association between women’s empowerment and lower rates of child undernutrition in sub-Saharan Africa. However, the relationship between women’s decision-making power and child undernutrition is less under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 29 publications
(38 reference statements)
6
25
0
Order By: Relevance
“…Other empowerment dimensions (i.e., access to healthcare, decision-making power, attitudes towards wife-beating by husband, and asset ownership) are insignificant, which suggests that the empowerment of women in arenas other than socioeconomic status may not help improving children’s health status of stunting and wasting. This finding is consistent with the findings of some previous studies that reported no statistically significant association between some women’s empowerment dimensions (e.g., decision making, access to healthcare, beating or domestic violence) and children’s nutritional status of height-for-age and weight-for-height [ 16 , 26 , 29 , 55 , 71 ]. For example, [ 16 ] found no significant association between women’s empowerment in agriculture and child health status in Northern Ghana.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Other empowerment dimensions (i.e., access to healthcare, decision-making power, attitudes towards wife-beating by husband, and asset ownership) are insignificant, which suggests that the empowerment of women in arenas other than socioeconomic status may not help improving children’s health status of stunting and wasting. This finding is consistent with the findings of some previous studies that reported no statistically significant association between some women’s empowerment dimensions (e.g., decision making, access to healthcare, beating or domestic violence) and children’s nutritional status of height-for-age and weight-for-height [ 16 , 26 , 29 , 55 , 71 ]. For example, [ 16 ] found no significant association between women’s empowerment in agriculture and child health status in Northern Ghana.…”
Section: Discussionsupporting
confidence: 92%
“…For example, [ 16 ] found no significant association between women’s empowerment in agriculture and child health status in Northern Ghana. Using cross-sectional data from the 2013–14 DHS data, in the Democratic Republic of Congo [ 71 ], found women’s decision making power were not significantly associated with stunting or wasting in children. Similarly, [ 32 ] found that women’s decision making authority has a weak effect on children’s health in sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 99%
“…The socioeconomic factors were significantly associated with stunting in our study as was in many studies conducted previously in developing countries [50,51]. Children who belonged to poor households, scheduled tribe category or resided in rural areas were more likely to be stunted than their counterparts from wealthy, urban households and other castes.…”
Section: Discussionsupporting
confidence: 81%
“…Children who belonged to poor households, scheduled tribe category or resided in rural areas were more likely to be stunted than their counterparts from wealthy, urban households and other castes. Also, Males were found to be more prone to stunting than females [50,52]. The children whose mothers, aged more than 25 years, had completed secondary or higher level of schooling were less likely to be stunted than those who were younger than 25 years and only at primary level or no education.…”
Section: Discussionmentioning
confidence: 93%
“…Akombi et al [9] concluded in their study that countries in East and West Africa bore the greatest burden of malnutrition in the SSA region. Malnutrition is expressed through either undernutrition (the most common in less developed countries), a situation of low protein-energy intake [10] (which usually manifests at different anthropometric indices in stunting, wasting and underweight), and/or overnutrition, which is commonly associated with too great an intake of protein-energy (a situation widely associated with developed society, but of less concern in the developing countries [11], perhaps a dangerous position to assume especially in Africa).…”
Section: Introductionmentioning
confidence: 99%